Survival Strategies of Micro Business Owners in Ternate City in Facing Urban Economic Pressure - Ciremai, Rahmadani Putri; Hi.Umar, Dian Ariyani; Karim, Amalia; Djainal, Mudrika M. Zen; Mahading, Finasti; La Eda, Akmal; Hi Hukum, Asmiah (Electronic Journal of Education, Social Economics and Technology, 2025)
Urban economic development brings various pressures for micro-business owners, particularly in island regions like Ternate City. Rising inflation, increasing cost of living, intensifying business competition, and changing consumption patterns of urban residents pose real challenges to the sustainability of micro-enterprises with limited capital and adaptive capacity. This research aims to analyze the survival strategies employed by micro-business owners in Ternate City in the face of urban economic pressures. The research uses a descriptive qualitative approach with data collection techniques including in-depth interviews, field observations, and documentation from nine micro-enterprises operating in the culinary, small trade, and service sectors. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing. The research results indicate that micro-business owners face economic pressure in the form of rising raw material prices, increasing operational costs, business competition, and declining consumer purchasing power. To survive, business owners are implementing cost efficiency strategies, product diversification, simple use of digital technology, operational flexibility, and strengthening social networks and family support. However, the effectiveness of this strategy is influenced by supporting and hindering factors, such as capital limitations, digital literacy, and policy access. This research underscores the importance of micro-enterprise empowerment policies that are adaptable to the dynamics of the urban economy.